Formulasi dan Uji Efektivitas Sediaan Lip cream dari Ekstrak Etanol Biji Buah Merah (Pandanus conoideus L) sebagai Pewarna Alami dengan Menggunakan Metode DPPH (1,1-Difenil-2-Pikrihidrazil) - Nur Baetty Primadani; Rugayyah Alyidrus; Nurfiddin Farid; Nielma Auliah (LPPM Universitas Abdurrab, 2023)
Formulation and Effectiveness Test of Lip Cream Preparations from Ethanol Extract of Red Fruit Seeds (Pandanus conoideus L) as A Natural Dye Using The DPPH (1,1-Diphenyl-2-Pikrihidrazil) Method. Red fruit seeds are botanical specimens that possess keratenoid chemicals, specifically b-carotene and a-carotene, which exhibit antioxidant properties. The objective of this study is to develop a stable Lipcream formulation and measure the IC50 value of the lipcream prepared from the ethanol extract of red fruit seeds (Pandanus conoideus L), which has antioxidant properties. An experimental research approach utilizing a solvent maceration technique with a solvent concentration of 96%. The obtained concentrated extract was subjected to rotation, followed by the fabrication of solutions with concentrations of 2%, 4%, and 6%, utilizing beeswax as a thickening agent. Kaolin is used as a texturizer. The emollients used are castor oil, cetyl alcohol, and dimethicon. Methyl paraben and propyl paraben are utilized as preservatives. Titanium dioxide serves as a pigment. The scent of vanilla. The preparation was evaluated by a cycling test consisting of 6 cycles over a period of 12 days. Organoleptic observations revealed a semi-solid texture, cream-like form, and a vanilla scent. The homogeneity test yielded consistent results, with pH measurements exceeding 0.05p, spreadability test results surpassing 0.05p, and adhesiveness test results meeting the specified standards. In addition to doing antioxidant testing, the DPPH method is employed using a UV-Vis spectrophotometer. The research findings indicate that the ethanol extract derived from red fruit seeds (Pandanus conoideus L) can be effectively made into a stable lip cream formulation, both in terms of its physical and chemical properties. The IC50 values obtained from the lip cream formulation including the ethanol extract of red fruit seeds (Pandanus conoideus L) were 59,496 ppm, 52,817 ppm, and 5,581 ppm, respectively. Formula 3 contains the most potent antioxidant value among all lip cream preparations.